Evaluasi Sikap Mahasiswa Ilmu Komputer terhadap Etika dan Kebijakan AI (Studi Kasus: STMIK Lombok) - Wianata Firdaus; Siti Maulinda Safira; Fahdilatul Islamin (Lembaga Publikasi Ilmiah Nusantara, 2025)
The rapid development of artificial intelligence (AI) has given rise to various ethical and policy implications that aspiring professionals in the information technology field need to understand. This study aims to evaluate the attitudes of Computer Science students towards the ethics and policies of AI use, using a case study at STMIK Lombok. The research approach used a quantitative descriptive method by distributing questionnaires to 120 active student respondents. The research instrument was developed based on indicators of understanding technology ethics, awareness of the social impacts of AI, perceptions of regulations, and professional responsibility in AI applications. Data were analyzed using descriptive statistics and correlation tests to determine the relationship between the level of ethical knowledge and attitudes towards AI policies. The results show that most students have a fairly good understanding of AI ethics, but still have a low understanding of the formal policies and regulations governing the application of AI in Indonesia. The main factors influencing positive attitudes towards AI ethics are academic experience and exposure to global technology issues. This study emphasizes the importance of integrating technology ethics and digital policy courses into the Computer Science curriculum so that students can become socially and professionally responsible AI developers.